Exploring the impact of the COVID-19 pandemic in Euroleague Basketball - Paulauskas, Rûtenis; Stumbras, Mykolas; Coutinho, Diogo; Figueira, Bruno (Frontiers in Psychology, 2022)
The aim of this study was to understand how COVID-19 training and playing conditions affected the performance of Euroleague Basketball players. Using a non-participant observation analysis, the study compared the seasons before lockdown (2018-19 and 2019-20; Pre-pandemic) with the season after restart (2020-21; Pandemic). Paired t-tests and Wilcoxon tests were applied for variables with normal and non-normal distributions, respectively. Results revealed significant changes (p<0.05) in several offensive and defensive performance-related variables during pandemic times (without attendance): free-throw attempts, free-throw percentage, turnovers, three-point attempt rate, fouls (small effect sizes – ES), points and possessions (trivial ES). The pre-pandemic HA (70%) significantly decreased after the lockdown, with games played with no crowd (~51%; p = 0.018, large ES). The one-sample t-test showed that the HA after the COVID-19 interruption was not significantly greater than 50%, indicating that the HA did not endure during the pandemic condition. Although significant differences between home and away teams were found for most performance-related variables (excepting turnovers) in both pre-pandemic and pandemic conditions, variations of the relative HA were only significant for free-throw attempts (large ES), points (medium ES) and turnovers (medium ES). The results of this study showed that performance variables were affected by the Covid-19 lockdown. Thus, these findings may help coaches, players and referees to counteract unwanted competitive events and improve their overall performance regardless of the contextual/situational circumstances encountered.